Twenty‐four–hour normothermic perfusion of discarded human kidneys with urine recirculation. Issue 1 (20th June 2018) - Weissenbacher, Annemarie; Lo Faro, Letizia; Boubriak, Olga; Soares, Maria F.; Roberts, Ian S.; Hunter, James P.; Voyce, Daniel; Mikov, Nikolay; Cook, Andrew; Ploeg, Rutger J.; Coussios, Constantin C.; Friend, Peter J.
Abstract : Transportable normothermic kidney perfusion for 24 hours or longer could enable viability assessment of marginal grafts, increased organ use, and improved transplant logistics. Eleven clinically declined kidneys were perfused normothermically, with 6 being from donors after brain death (median cold ischemia time 33 ± 36.9 hours) and 5 being from donors after circulatory death (36.2 ± 38.3 hours). Three kidneys were perfused using Ringer's lactate to replace excreted urine volume, and 8 kidneys were perfused using urine recirculation to maintain perfusate volume without fluid replenishment. In all cases, normothermic perfusion either maintained or slightly improved the histopathologically assessed tubular condition, and there was effective urine production in kidneys from both donors after brain death and donors after circulatory death (2367 ± 1798 mL vs 744.4 ± 198.4 mL, respectively; P = .44). Biomarkers, neutrophil gelatinase–associated lipocalin, and kidney injury molecule‐1 were successfully detected and quantified in the perfusate. All kidneys with urine recirculation were readily perfused for 24 hours (n = 8) and exhibited physiological perfusate sodium levels (140.7 ± 1.2 mmol/L), while kidneys without urine recirculation (n = 3) achieved a reduced normothermic perfusion time of 7.7 ± 1.5 hours and significantly higher perfusate sodium levels (159.6 ± 4.63 mmol/:, P < .01). Normothermic machine perfusion of human kidneys for 24 hours appears to be feasible, and urine recirculation was found to facilitate the maintenance of perfusate volume and homeostasis. Abstract : Normothermic machine perfusion of human kidneys for 24 hours is feasible, and urine recirculation facilitates maintenance of perfusate volume and homeostasis.